The complete solar house - Cassiday, Bruce (New York : Dodd, Mead, 1977)
Not a how-to-do-it manual, this book is an overview of the uses of solar energy in the home, a discussion of hot water systems, solar collectors, installation costs, etc.
Includes index.
Keywords: Solar houses